PENGARUH GAYA HIDUP, PENGETAHUAN KONSUMEN DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN MITSUBISHI DI PT. SUN STAR MOTOR KEDIRI - Hawin Anam Fadhlullah; Rois Arifin; M Hufron (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe research was quantitative research involving the variable lifestyle, knowledge level, reference group, and decision to purchase. Data of the research was collected through interview, observations and get 55 respondents of the customers of PT. Sun Star Motor Kediri . Data was then analyzed using multiple linier regression using SPSS for Windows.The result of multiple linier regression analyses showed that Y= -2.663+ 0,305 + 0,391 + 0,472 + e. Based research findings it can be concluded that there is influence between lifestyle, knowledge level, and reference group to the decision to purchasesimultaneously or partially. Then PT. Sun Star Motor Kediri needs to implement strategic steps towards matters relating to variables that influence consumer purchasing decisions. Keywords: lifestyle, knowledge level, reference group, and decision to purchase